The Fund's Income Position for FY 2017 : Actual Outcome. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper reports the Fund's income position for FY 2017 following the closing of the Fund's accounts for the financial year and completion of the external audit. Total FY 2017 net income, including income from surcharges, amounted to SDR 1.9 billion or about SDR 258 million higher than estimated in April, reflecting mainly a larger than anticipated gain reported under IAS 19 (the accounting standard for employee benefits). GRA net income for FY 2017 was about SDR 1.49 billion and has been placed to the Fund's reserves. In accordance with decisions taken in April 2017, a net transfer of currencies amounting to SDR 1.41 billion was made in August 2017 from the GRA to the Investment Account. The placement of the net income to the Fund's reserves has further strengthened the Fund's precautionary balances, which reached SDR 16.7 billion at the end of FY 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Income; PP; SDR Billion; SDR Department; United States